2014
DOI: 10.1017/s0263574714002653
|View full text |Cite
|
Sign up to set email alerts
|

Analytical modeling and analysis of the clearance induced orientation error of the RAF translational parallel manipulator

Abstract: SUMMARYThis paper deals with the analytical modeling and the analysis of the orientation error of the RAF translator due to the clearances in the joints. This model presents the orientation error as a function of the nominal pose, the external load applied to the platform, the manipulator structural parameters, and the joints clearances. Based on this model, an algorithm is developed in order to map the pose error within a desired workspace of the manipulator. It is shown that the orientation error variation d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…For the RAF manipulator, the static model is already developed ( [11,29] present more details). If a τ ext = [F M] T is applied to O p , the forces will be transmitted by the SPS legs and the moments will be supported by the PKL legs (Fig.…”
Section: Static Model Of Raf Manipulatormentioning
confidence: 99%
See 2 more Smart Citations
“…For the RAF manipulator, the static model is already developed ( [11,29] present more details). If a τ ext = [F M] T is applied to O p , the forces will be transmitted by the SPS legs and the moments will be supported by the PKL legs (Fig.…”
Section: Static Model Of Raf Manipulatormentioning
confidence: 99%
“…The accuracy of parallel mechanism can be altered by the uncertainties of the geometric parameters, joint clearances or both of them [4,5,[8][9][10][11][12][13][14]. Indeed, Al-Widyan et al [4] proposed a statistical approach to determine the optimum clearances of the unactuated cylindrical joints for the 3-DOF spherical manipulators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The paper addressed the kinematic accuracy problem of the proposed new parallel robot with three legs due to the location of the U joint errors, clearance, and driving errors. Chouaibi's paper showed that the orientation error variation depends essentially on the parallelogram configuration of the passive legs out of its plane [13].…”
Section: Introductionmentioning
confidence: 99%
“…The problem of modeling joints with clearance in the context of multibody dynamics has been the subject of extensive studies during the last few decades. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Dubowsky and Freudenstein 16,17 formulated an impact pair model to predict the dynamic response of an elastic mechanical joint with clearance. Earles and Wu 18 introduced a model based on permanent contact condition.…”
Section: Introductionmentioning
confidence: 99%